2021
DOI: 10.1007/s11356-021-17197-9
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress is involved in the activation of NF-κB signal pathway and immune inflammatory response in grass carp gill induced by cypermethrin and/or sulfamethoxazole

Abstract: At present, the concentration of environmental pollutants, such as pesticides and antibiotics exposed in environment, especially in aquatic environment is increasing. These contaminants are exposed through aquatic environment to sh and ultimately accumulate in humans. Research on environmental pollutants has exploded in the past two years. However, there are still few studies on the combined effects of pesticides and antibiotics on sh, especially on sh gills. A separate analysis of the toxic effects caused by … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 88 publications
0
8
0
Order By: Relevance
“…24,25 Studies conducted to investigate the mechanism of these effects have shown that CYP causes damage in different tissues by causing oxidative stress, inflammation and apoptosis. 6,7,26,27 However, the mechanism of action on gastric tissue is unclear. Considering this information, this study was conducted to investigate the potential protective effect of CYP on gastric damage caused by oxidative stress, inflammation, ER stress, apoptosis and autophagy.…”
Section: Evaluation Of Histopathological Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…24,25 Studies conducted to investigate the mechanism of these effects have shown that CYP causes damage in different tissues by causing oxidative stress, inflammation and apoptosis. 6,7,26,27 However, the mechanism of action on gastric tissue is unclear. Considering this information, this study was conducted to investigate the potential protective effect of CYP on gastric damage caused by oxidative stress, inflammation, ER stress, apoptosis and autophagy.…”
Section: Evaluation Of Histopathological Resultsmentioning
confidence: 99%
“…Studies in the literature suggest that ROS-mediated oxidative stress is under the toxic effect of pesticides. 26,27 Oxidative stress occurs because of the disruption of the balance between the ROS and antioxidant systems. In studies, the degree of oxidative stress damage caused by CYP has been reported by looking at the accumulation of lipid peroxidation.…”
Section: Evaluation Of Histopathological Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gill is an important organ for oxygen exchange, salinity sensing, acid–base balance, and nitrogenous waste excretion. When subjected to abiotic stress, such as saline and alkaline water, gill can initiate signal cascades to enhance the tolerance (Aruna et al 2021 ; Chang et al 2021 ; Li et al 2021 ). Thus, gill was chosen as the research object during the analysis of stress response.…”
Section: Discussionmentioning
confidence: 99%
“…Despite their widespread use, there is growing interest in their neurotoxic effects on humans. Through extensive research, it has been accepted that CPM exposure to humans results in neurotoxicity and neurodegenerative diseases [ 5 , 6 ]. Insecticides can interrupt the function of vital organs in the body and bring about endocrine, cardiovascular, reproductive, renal, and nervous system disorders [ 7 ].…”
Section: Introductionmentioning
confidence: 99%